Language as a Status Symbol of Power in Social Interactions at a Multicultural School in the City of Medan - Ahmed Fernanda Desky; Pujiati Pujiati; Muba Simanihuruk; Rizabuana Ismail; Ria Manurung (Jurnal Ilmu Sosial dan Ilmu Politik, 2017)
One’s habit in language use is inﬂuenced by daily social life structures thereby creating diﬀerent interaction patterns both individually or as a group. Sociology of language critically analyzes the use of language as a symbol of power which dominates the arena in a multicultural school. This research utilizes mixed methods as it is considered capable of ﬁnding and answering the issues and problems under examination. The location of research was Sultan Iskandar Muda High School which is the only multicultural education curriculum based pilot school in the city of Medan. The informants in this study were the principal, teachers, and students while the respondents were samples of high school students totaling 86 individuals. Research results show that one’s power in language use is determined by one’s interest in using language. School power and individual power has diﬀerent portions when positioning one’s self during interactions. Although power is coercive in nature, the community must submit to rules of the school. The power of the school in determining language emphasizes values of nationalism, which is diﬀerent to individual or group power which adjusts the language to the situation at hand so that relations of language use has its own portion of interaction in the multicultural school.